The association of calligraphy activities with peace of mind, stress self-management, and perceived health status in older adults - Wang, Jianing; Tang, Kaizhi (Frontiers in Psychology, 2024)
Introduction: Calligraphy, as a form of mindful practice, encourages focus, creativity, and relaxation, which collectively contribute to a more peaceful mental state. Through regular engagement in calligraphy, older adults can develop better coping mechanisms for stress, leading to more effective selfmanagement of daily stressors. This enhanced ability to manage stress can reduce the overall burden on their mental and physical health, promoting a more positive outlook on life.Methods: This study employed convenience sampling and snowball sampling to select 246 older adults aged 60-70 from Changsha, China, in March 2024 as valid samples. AMOS v.23 was used to construct a structural equation model to validate the hypotheses.The study found a significant positive correlation between calligraphy activities and peace of mind/stress self-management. There is also a significant positive correlation between peace of mind/stress self-management and perceived health status. Additionally, peace of mind and stress selfmanagement act as mediators between calligraphy activities and perceived health status.Discussion: This indicates that calligraphy activities not only contribute to the psychological wellbeing of older adults but also indirectly enhance their positive perception of their own health by improving their mental state. Consequently, such activities can be an integral part of holistic health interventions aimed at enhancing the quality of life and overall health of older adults.